Exploring preference for, and uptake of, rural medical internships, a key issue for supporting rural training pathways - Matthew R. McGrail; Belinda G. O'Sullivan; Deborah J. Russell; Muntasirur Rahman (BMC, 2020)
Abstract Background Improved medical care access for rural populations continues to be a major concern. There remains little published evidence about postgraduate rural pathways of junior doctors, which may have strong implications for a long-term skilled rural workforce. This exploratory study describes and compares preferences for, and uptake of, rural internships by new domestic and international graduates of Victorian medical schools during a period of rural internship position expansion. Methods We used administrative data of all new Victorian medical graduates' location preference and accepted location of internship positions for 2013-16. Associations between preferred internship location and accepted internship position were explored including by rurality and year. Moreover, data were stratified between 'domestic graduates' (Australian and New Zealand citizens or permanent residents) and 'international graduates' (temporary residents who graduated from an Australian university). Results Across 2013-16, there were 4562 applicants who filled 3130 internship positions (46% oversubscribed). Domestic graduates filled most (69.7%, 457/656) rural internship positions, but significantly less than metropolitan positions (92.2%, p < 0.001). Only 20.1% (551/2737) included a rural location in their top five preferences, less than for international graduates (34.4%, p < 0.001). A greater proportion of rural compared with metropolitan interns accepted a position not in their top five preferences (36.1% versus 7.4%, p < 0.001). The proportion nominating a rural location in their preference list increased across 2013-2016. Conclusions The preferences for, and uptake of, rural internship positions by domestic graduates is sub-optimal for growing a rural workforce from local graduates. Current actions that have increased the number of rural positions are unlikely to be sufficient as a stand-alone intervention, thus regional areas must rely on international graduates. Strategies are needed to increase the attractiveness of rural internships for domestic students so that more graduates from rural undergraduate medical training are retained rurally. Further research could explore whether the uptake of rural internships is facilitated by aligning these positions with protected opportunities to continue vocational training in regionally-based or metropolitan fellowships. Increased understanding is needed of the factors impacting work location decisions of junior doctors, particularly those with some rural career intent.